2017
DOI: 10.1021/acssuschemeng.7b00985
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Elusive Intermediates in Carbohydrate Conversion: A Dynamic Ensemble of Acyclic Glucose–Catalyst Complexes

Abstract:  Users may download and print one copy of any publication from the public portal for the purpose of private study or research.  You may not further distribute the material or use it for any profit-making activity or commercial gain  You may freely distribute the URL identifying the publication in the public portal If you believe that this document breaches copyright please contact us providing details, and we will remove access to the work immediately and investigate your claim.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
23
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(23 citation statements)
references
References 33 publications
0
23
0
Order By: Relevance
“…Specifically, dissolution dynamic nuclear polarization for enhancing NMR signals (D-DNP-NMR) 11 has shown promise in detecting previously elusive states in bio-and chemocalytic carbohydrate conversion. [12][13][14][15] This approach generates substrates with hyperpolarized nuclear spins and triggers reactions by rapid injection of the hyperpolarized substrate to a chemical or biological catalyst, while providing a signal increase by DNP on the order of 10 000. [16][17][18] Synergistic applications of D-DNP and conventional NMR techniques to characterize catalytic cycles on complementary time scales have remained very rare, however.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Specifically, dissolution dynamic nuclear polarization for enhancing NMR signals (D-DNP-NMR) 11 has shown promise in detecting previously elusive states in bio-and chemocalytic carbohydrate conversion. [12][13][14][15] This approach generates substrates with hyperpolarized nuclear spins and triggers reactions by rapid injection of the hyperpolarized substrate to a chemical or biological catalyst, while providing a signal increase by DNP on the order of 10 000. [16][17][18] Synergistic applications of D-DNP and conventional NMR techniques to characterize catalytic cycles on complementary time scales have remained very rare, however.…”
mentioning
confidence: 99%
“…[16][17][18] Synergistic applications of D-DNP and conventional NMR techniques to characterize catalytic cycles on complementary time scales have remained very rare, however. 13,19 The current work aims to extend the mechanistic and kinetic understanding of carbohydrate dehydration pathways. D-DNP NMR was employed to detect transient early intermediates in the Lewis acid catalysed conversion of fructose.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…7 The third study also serves as an example of dDNP NMR for monitoring carbohydrate conversion, and the presence of an open-chain configuration of glucose bound to the molybdate-catalyst was detected. 8 These studies all demonstrated the use of dDNP NMR to observe and describe reaction intermediates, and applying the method for glycosidases represents the possibility to further understand the mechanisms and transglycosylation abilities of the enzymes.…”
Section: Introductionmentioning
confidence: 97%
“…Exceptions to this are ketoses such as fructose, in which the anomeric position, which is also usually the position of interest, is quaternary with a long T1, and consequently fructose has been used for in vivo murine studies. 9 For aldoses it is necessary to utilize 2 H labelling to elongate the T1 of the positions of interest, and [U-2 H;U-13 C]glucose has been used for several studies, 8,[10][11][12][13] but only one of these focused on the mechanisms of a single enzyme, namely phosphorylation of glucose by hexokinase. 13 Here we demonstrate the utility of dDNP NMR for increasing the understanding of carbohydrate converting enzymes, and the enzyme chosen as model enzyme is the lacZ β-galactosidase, as it is well characterized.…”
Section: Introductionmentioning
confidence: 99%